2019
DOI: 10.1093/cvr/cvz176
|View full text |Cite
|
Sign up to set email alerts
|

Role of the lysyl oxidase enzyme family in cardiac function and disease

Abstract: Heart diseases are a major cause of morbidity and mortality world-wide. Lysyl oxidase (LOX) and related LOX-like (LOXL) isoforms play a vital role in remodelling the extracellular matrix (ECM). The LOX family controls ECM formation by cross-linking collagen and elastin chains. LOX/LOXL proteins are copper-dependent amine oxidases that catalyse the oxidation of lysine, causing cross-linking between the lysine moieties of lysine-rich proteins. Dynamic changes in LOX and LOXL protein-expression occur in a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 145 publications
0
30
0
Order By: Relevance
“…As glomerulosclerosis remained elevated in that group, it is likely that such improvement in filtration is driven by haemodynamic mechanisms. Supporting this hypothesis, a number of studies suggested important roles of LOXs in cardiac function and vascular stiffness 41 , 42 , which could influence blood flow to the kidney. A limitation of this study is that renal haemodynamic parameters have not been measured to further elucidate this mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…As glomerulosclerosis remained elevated in that group, it is likely that such improvement in filtration is driven by haemodynamic mechanisms. Supporting this hypothesis, a number of studies suggested important roles of LOXs in cardiac function and vascular stiffness 41 , 42 , which could influence blood flow to the kidney. A limitation of this study is that renal haemodynamic parameters have not been measured to further elucidate this mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…LOX (lysyl oxidase) showing location of the Tyr250 and Thr341 variants within the catalytic domain of the C‐terminal motif, which is highly conserved across species. LOX‐family catalysis is vital for elastin and collagen crosslinking in multiple tissues 18 [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…The LOX pathway that works during the process is leukotrienes and hydroperoxy fatty acids [16,17]. Nowadays, LOX has become a target for inflammatory therapy [18]. The previous study showed LOX as an anticancer [19].…”
Section: Introductionmentioning
confidence: 99%